Estimating the burden on general practitioner services in England from increases in respiratory disease associated with seasonal respiratory pathogen activity. Issue 11 (4th July 2018) - Morbey, R. A.; Elliot, A. J.; Harcourt, S.; Smith, S.; de Lusignan, S.; Pebody, R.; Yeates, A.; Zambon, M.; Smith, G. E.
Abstract: Understanding the burden of respiratory pathogens on health care is key to improving public health emergency response and interventions. In temperate regions, there is a large seasonal rise in influenza and other respiratory pathogens. We have examined the associations between individual pathogens and reported respiratory tract infections to estimate attributable burden. We used multiple linear regression to model the relationship between doctor consultation data and laboratory samples from week 3 2011 until week 37 2015. We fitted separate models for consultation data with in-hours and out-of-hours doctor services, stratified by different age bands. The best fitting all ages models ( R 2 > 80%) for consultation data resulted in the greatest burden being associated with influenza followed by respiratory syncytial virus (RSV). For models of adult age bands, there were significant associations between consultation data and invasive Streptococcus pneumoniae. There were also smaller numbers of consultations significantly associated with rhinovirus, parainfluenza, and human metapneumovirus. We estimate that a general practice with 10 000 patients would have seen an additional 18 respiratory tract infection consultations per winter week of which six had influenza and four had RSV. Our results are important for the planning of health care services to minimise the impact of winter pressures. Respiratory pathogen incidence explains over 80% of seasonal variation in respiratory consultation data. Influenza and RSV are associated with the biggest seasonal rises in respiratory consultation counts. A third of consultation counts associated with respiratory pathogens were due to influenza.